Within-individual variability in self-concepts and personality states: Applying density distribution and situation-behavior approaches across cultures - Church, A. Timothy (Animo Repository, 2013)
Within-individual variability in self-concepts and everyday personality states and affects was investigated in two experience sampling studies using density distribution and situation-behavior approaches. In all seven cultures sampled, within-individual variability was substantial and self-concept and personality state variability exhibited moderate convergence. Variability in personality and affect states was moderately predicted by perceived need satisfaction in the situations. The density distribution and situation-behavior approaches were moderately convergent in identifying the most variable individuals, but the pattern of cultural differences differed in the two methods. Contrary to cultural psychology perspectives, cultural differences in within-individual variability did not consistently correspond to cultural differences in individualism-collectivism, dialecticism, or tightness. © 2013 Elsevier Inc.